Omissions are not accidents : modern apophaticism from Henry James to Jacques Derrida - Knight, Christopher J., 1952- (University of Toronto Press, 2010)
In Omissions Are Not Accidents, Christopher J. Knight analyzes the widespread apophaticism in texts from the late nineteenth to the late twentieth century.